The school of doubt : skepticism, history and politics in Cicero's Academica - Cappello, Orazio, (Brill Studies in Skepticism, 2019)
The School of Doubt conducts a close philological and philosophical reading of Cicero's Academica , a fragmentary work on sense-perception and Academic history written in the wake of Caesar's victory in the civil wars (45 BCE). Focusing in turn on the author's letters discussing the process of composition, the historiographical treatment of the Platonic tradition and the critical exploration of philosophical doubt, this volume presents Cicero as an original and sophisticated historian of philosophy and a radical figure in Western skeptical thought. Widely misconstrued as a technical treatise and a mere chronicle of the Greek debates on which it draws, the Academica here emerges as a key work in the evolution of Ciceronian philosophy and of ancient skepticism - and one that responds directly to the disintegration of Republican Rome.